If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) + 2(x + -7) = 38 Reorder the terms: 3(4 + x) + 2(x + -7) = 38 (4 * 3 + x * 3) + 2(x + -7) = 38 (12 + 3x) + 2(x + -7) = 38 Reorder the terms: 12 + 3x + 2(-7 + x) = 38 12 + 3x + (-7 * 2 + x * 2) = 38 12 + 3x + (-14 + 2x) = 38 Reorder the terms: 12 + -14 + 3x + 2x = 38 Combine like terms: 12 + -14 = -2 -2 + 3x + 2x = 38 Combine like terms: 3x + 2x = 5x -2 + 5x = 38 Solving -2 + 5x = 38 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 5x = 38 + 2 Combine like terms: -2 + 2 = 0 0 + 5x = 38 + 2 5x = 38 + 2 Combine like terms: 38 + 2 = 40 5x = 40 Divide each side by '5'. x = 8 Simplifying x = 8
| 4x+6y+2=0 | | [12w+1]=3w-2 | | [7x-2]=5 | | 7X/6*6 | | 3t+5(8-t)=24-t | | -2-5=-3+x | | x-4(6)=9 | | 2x+5.7=5 | | w+(-15)=-15 | | (8x-2)(x+1)=0 | | b+(-2)=38 | | 29+2y-8=12y-14-5y | | m-(-2)=-5 | | 2014-1987= | | b-(-7)=-1 | | y=2000(2)2 | | 4t-6=0 | | 3(v-2)-8=-4(-7v+5)-9v | | x-6=-2+3 | | 6(x-4)=6(9) | | 6z-18-4+21=-12z+24-14z | | 9x+3(2)=-3 | | 9x+3(2)= | | (5x+7)+(6x+30)= | | 3(0)+7y=4 | | 5/9(77-31) | | 15-(w-5)= | | 2(t-3)-5=7 | | 6p-12=2p+6 | | 6-4-7+4-7+4-2= | | c-3=21 | | d-7=12 |